2020
DOI: 10.1038/s41598-020-75744-9
|View full text |Cite
|
Sign up to set email alerts
|

Local ancestry inference provides insight into Tilapia breeding programmes

Abstract: Tilapia is one of the most commercially valuable species in aquaculture with over 5 million tonnes of Nile tilapia, Oreochromis niloticus, produced worldwide every year. It has become increasingly important to keep track of the inheritance of the selected traits under continuous improvement (e.g. growth rate, size at maturity or genetic gender), as selective breeding has also resulted in genes that can hitchhike as part of the process. The goal of this study was to generate a Local Ancestry Interence workflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Genome sequences are composed of four nucleotides, typically represented with the letters: A, T, C and G. While the majority of genomic positions are fixed across individuals of the same species, a small fraction is known to be variable. Most of these positions are single-nucleotide polymorphisms (SNPs) that have two variants or forms, which allows for a binary encoding with a common or majority variant (encoded as a zero) shared among the majority of individuals and a minority or alternative variant (encoded as a one) (Avallone et al, 2020;Ioannidis et al, 2020;Kumar et al, 2020;Maples et al, 2013;Thornton and Bermejo, 2014).…”
Section: Genomic Data and Its Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequences are composed of four nucleotides, typically represented with the letters: A, T, C and G. While the majority of genomic positions are fixed across individuals of the same species, a small fraction is known to be variable. Most of these positions are single-nucleotide polymorphisms (SNPs) that have two variants or forms, which allows for a binary encoding with a common or majority variant (encoded as a zero) shared among the majority of individuals and a minority or alternative variant (encoded as a one) (Avallone et al, 2020;Ioannidis et al, 2020;Kumar et al, 2020;Maples et al, 2013;Thornton and Bermejo, 2014).…”
Section: Genomic Data and Its Applicationsmentioning
confidence: 99%
“…LAI is the prediction of the ancestral origin for each piece of an individual's genome. LAI has become increasingly important in the field of genomic data processing (Martin et al, 2017;Raghavan et al, 2015;Thornton and Bermejo, 2014) and its applications range from the study of human migrations and evolution (Avallone et al, 2020;Ioannidis et al, 2020;Padhukasahasram, 2014;Raghavan et al, 2015) to GWAS adjustment (Atkinson et al, 2021) and PRS prediction (Marnetto et al, 2020;Martin et al, 2017;Suarez-Pajes et al, 2021).…”
Section: Introduction To Laimentioning
confidence: 99%
“…The missense SNP (C/T) in exon II in Amhy , a previously suggested candidate sex‐determiner in Nile tilapia, was absent in the core Malaysian GIFT population (Taslima et al, 2020). The GIFT was thought to be a pure strain of Nile tilapia (as developed from the multiple Nile tilapia populations) but a very recent study has found that GIFT tilapia has mixed genetic structure in which Nile tilapia is the major contributor (95.98%) with the minor percentage from Mozambique (2.13%) and Blue tilapia (1.63%, Avallone et al, 2020).…”
Section: Parameters Commercial Dna Extraction Kit Salt‐isopropanol Pr...mentioning
confidence: 99%
“…The misalignment of the phenotypic and genotypic sex (using Amh exon VII deletion) of the GIFT tilapia in the present study could be because of the founder effect (due to transfer of limited numbers of broodstock from the WorldFish) or the GIFT tilapia population could be mixed with the existing Nile tilapia population in Bangladesh after transfer or may be the mixed/complex genetic architecture of the core GIFT tilapia population (developed from multiple populations of Nile tilapia). The very recent study found that the core GIFT tilapia population (Penang, Malaysia) is not a pure strain of Nile tilapia and has a very close association with the Nile tilapia including a very few percentage of gene introgression from Blue and Mozambique tilapia (Avallone et al, 2020; Bartie et al, 2020). Based on the genotypic and phenotypic association analysis in this study, the GIFT tilapia in BFRI stock was found to be maintained their genetic purity than the GIFT stock in commercial farm.…”
Section: Parameters Commercial Dna Extraction Kit Salt‐isopropanol Pr...mentioning
confidence: 99%